# How do you solve #-4(-d-4)=-4d+6(2d+6)#?

##### 1 Answer

Jan 12, 2017

#### Explanation:

The first step is to distribute brackets on both sides of the equation.

#rArr4d+16=-4d+12d+36# simplifying right side.

#4d+16=8d+36# Collect terms in d, on the left side and numeric values on the right.

subtract 8d from both sides.

#4d-8d+16=cancel(8d)cancel(-8d)+36#

#rArr-4d+16=36# subtract 16 from both sides.

#-4dcancel(+16)cancel(-16)=36-16#

#rArr-4d=20# To solve for d, divide both sides by - 4

#(cancel(-4) d)/cancel(-4)=20/(-4)#

#rArrd=-5#

#color(blue)"As a check"#

#"left side " =-4(-(-5)-4)=-4xx1=-4#

#"right side " =(-4xx-5)+6(2xx(-5)+6)#

#=20+6(-10+6)=20+6(-4)=20-24=-4#

#"Thus both sides " =-4#

#rArrd=-5" is the solution"#